Evaluation of Biomass Energy Policy Implementation in Indonesia to National Defense Support - Putri Azmi Millatie; Rahmat Hidayat; Suyono Thamrin; Lailatul Fajriyah (CV. AFDIFAL MAJU BERKAH, 2024)
Biomass energy is recognized as having strategic potential in overcoming energy security challenges and its participation to reduce the impact of environmental problems. The research-purpose is to evaluate how implementing a biomass energy policy can support national defense and sustainability. Through the framework of the literature, this study describes the concept of biomass energy and examines its relation to national defense. Energy policy analysis and reversed with energy security in Indonesia are also obtained from the reflection of the literature. The results show that biomass energy can strengthen the security of a country's energy supply by diversifying energy sources and reducing dependence on imported fossil fuels. This will support the operational defense system in dealing with fluctuations in energy prices and supplies. The implementation of biomass energy also has the potential to increase national energy independence, reduce the risk of energy supply disruptions, and strengthen national resilience. Utilization of biomass energy also contributes to improving climate change and negative environmental impacts. With the right technology, reductions in greenhouse gas emissions can be achieved, supporting environmental sustainability goals and securing the future of national defense